2022
DOI: 10.3390/app12020874
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Superconductivity in the Lanthanide Hydrides at Extreme Pressures

Abstract: Hydrogen-rich superhydrides are promising high-Tc superconductors, with superconductivity experimentally observed near room temperature, as shown in recently discovered lanthanide superhydrides at very high pressures, e.g., LaH10 at 170 GPa and CeH9 at 150 GPa. Superconductivity is believed to be closely related to the high vibrational modes of the bound hydrogen ions. Here, we studied the limit of extreme pressures (above 200 GPa) where lanthanide hydrides with large hydrogen content have been reported. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…The benefit of the Bose-Einstein condensate is amplifying microscopic quantum effects to visible macroscopic scales. Researchers are now able to condense more complex particles in the fermionic domain such as lanthanides [18], reactive metals implicated in high-temperature superconducting [19], and also in the bosonic domain, as quantum droplets comprised of bose-bose mixtures and dipolar quantum gases (supersolids) [20]. These kinds of condensate methods are used to solve localized wavefunctions with complex topological structures, and could be deployed more exploratively, for example, to study non-von Neumann architectures for information processing tasks, including to study associative memory in the brain [21].…”
Section: Condensatesmentioning
confidence: 99%
“…The benefit of the Bose-Einstein condensate is amplifying microscopic quantum effects to visible macroscopic scales. Researchers are now able to condense more complex particles in the fermionic domain such as lanthanides [18], reactive metals implicated in high-temperature superconducting [19], and also in the bosonic domain, as quantum droplets comprised of bose-bose mixtures and dipolar quantum gases (supersolids) [20]. These kinds of condensate methods are used to solve localized wavefunctions with complex topological structures, and could be deployed more exploratively, for example, to study non-von Neumann architectures for information processing tasks, including to study associative memory in the brain [21].…”
Section: Condensatesmentioning
confidence: 99%
“…Development of computational tools to predict crystal structures and calculate properties of materials using only theory methods has led to the emergence of ultra-high pressure generators. Nowadays, theoretical and experimental research on hydrogen-rich compounds covers binary hydrides materials formed by almost all elements, which also includes the lanthanum-based high-temperature superconducting material LaH 16 [8], and CeH 9 [9][10][11], CeH 16 [12,13] and YbH 10 . Research on these materials has found that binary lanthanide superconducting materials with high hydrogen content at high pressure are characterised with high symmetry and they exhibit a space group structure of hexagonal and cubic crystal systems under 200-300 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of development of computational tools for predicting crystal structures and calculating properties of materials, ultra-high pressure generators have emerged. Nowadays, theoretical and experimental research on hydrogen-rich compounds covers binary hydride materials formed by almost all elements, which also includes the lanthanum-based high-temperature superconducting material LaH 16 [8], as well as CeH 9 [9][10][11], CeH 16 , and YbH 10 [12,13]. Research on these materials has found that binary lanthanide superconducting materials with high hydrogen content at high pressure are characterized by high symmetry and that they exhibit a space group structure of hexagonal and cubic crystal systems under 200-300 GPa.…”
Section: Introductionmentioning
confidence: 99%